"What there is between us" : The Impact of Colonial Trauma on Female Identities and Relationships in Mornings in Jenin by Susan Abulhawa - Kukko, Milja (My University, 2025)
This thesis studies the impact of colonial trauma caused by the Israeli occupation of Palestine on the female characters in the novel Mornings in Jenin (2010). The aim is to determine how the trauma shapes the identities of three generations of women in the Abulheja family, their connections with each other and female friends. The themes studied follow the principles of postcolonial feminism as it is defined by Mills (1988) and Ball (2012), with the focus being on a narrative of the experiences of Palestinian women, produced by a female Palestinian-American author Susan Abulhawa. With its perspective and focus, the thesis aims to reinforce the existence of alternative narratives alongside the hegemonic Western narrative of Palestine. An account of the Palestinian reality under the Israeli occupation is given based on the reports from the United Nations Special Rapporteur on the occupied Palestinian territories, Francesca Albanese, and woven together with the story of Mornings in Jenin. The women: Dalia, Amal, and Sara, go through shared and individual traumatizing experiences including, but not limited to, traumatic losses of loved ones, physical violence, and exile. I also touch on the grief caused by the international silence and dismissal of Palestinian suffering. The accumulating, complex trauma results in broken and distorted identities, deep-seated sense of rootlessness and loneliness, issues with mental and physical health, attachment issues and the formation of intergenerational trauma, together with complicated, trauma reinforcing mother–daughter relationships and friendships. As the novel contains plenty of material, a broader character sample would be useful for future studies. An ecocritical perspective would allow access to the environmental impacts of war in a country heavily reliant on agriculture.
Keywords: Postcolonial feminism, colonial trauma, identity, intergenerational trauma, female relationships, Palestine, Susan Abulhawa, Mornings in Jenin